Alpha(1) antitrypsin deficiency and pulmonary emphysema - Jones, M. C. (1971)
An association between a genetically determined deficiency of the serum enzyme α(1) antitrypsin and pulmonary emphysema is now well established. Serum antitryptic activity was measured in 103 patients suspected of having emphysema. Eighty-seven fulfilled the diagnostic criteria for emphysema and, of these, 16 had deficient levels, 5 had intermediate levels, and 66 had normal levels. The results of clinical, radiographic, and physiological studies in each group were then compared. Characteristic features noted in the deficient group included onset of dyspnoea during the third or fourth decades and uniformly symmetrical radiographic lower zone involvement. Other factors such as sex distribution, cigarette smoking, and chronic bronchitis are discussed. Sixty-eight relatives of the 16 patients with deficient levels were also studied. The findings in these are compatible with an autosomal recessive mode of inheritance although difficulties in identifying the heterozygous state were encountered. Six relatives had deficient levels and of these three had emphysema.